Multilateralism, Sovereignty And Normative Change In World Politics - Acharya, Amitav (2016)
This paper examines the role of multilateralism in fostering and managing normative change in world politics, with specific regard to the fundamental norms of state sovereignty.1 Post-war multilateralism helped to define, extend, embed and legitimize a set of sovereignty norms, including territorial integrity, equality of states and nonintervention. Today, multilateral institutions are under increasing pressure to move beyond some of these very same principles, especially nonintervention, as part of a transformative process in world politics. Without multilateralism, it is highly doubtful that the post-war international order would have been so tightly and universally built upon the norms of sovereignty. And without multilateralism, argues this paper, transition from this normative order now would be difficult and chaotic, as may be already happening as a result of the Bush administration’s challenge to the current multilateral system. I begin by briefly outlining the idea of norms and normative change. Then, I offer an overview of the role of multilateralism, both at the global and regional levels, in promoting the norms of sovereignty in the post-war period. Next, I outline the pressures for normative change being faced by multilateral institutions in recent years. Finally, the paper analyzes how multilateralism is promoting normative change, with particular reference to the norm of nonintervention.